Unveiling Powell Basin’s Tectonic Domains and Understanding Its Abnormal Magnetic Anomaly Signature. Is Heat the Key? - Catalán, M.; Martos, Y. M.; Galindo-Zaldivar, J.; Perez, L. F.; Bohoyo, F. (Frontiers in Earth Science, 2020)
Rifting of continental lithosphere leading to oceanic basins is a complex process conditioned by different factors such as the rheology and thermal structure of the underlying lithosphere, as well as underlying asthenospheric dynamics. All these processes, which finally lead to oceanic domains, can better be recognized in small oceanic basins. Powell Basin is a small oceanic basin bounded to the north by the South Scotia Ridge, to the east by the South Orkney Microcontinent, and to the west by the Antarctic Peninsula. It was formed between the Oligocene and Miocene, however, its age is not well defined, among other reasons due to the small amplitude of its spreading magnetic anomalies. This basin is an ideal framework to analyze the different rifting and spreading phases, which leads from continental crust to the formation of an oceanic domain through different extensional regimes. To identify the different boundaries during the formation of Powell Basin from the beginning of the rifting until the end of the spreading, we use different data sources: magnetic, gravity, multichannel seismic profiles and bathymetry data. We use seismic and bathymetry data to estimate the Total Tectonic Subsidence (TTS). TTS has proven to be useful to delineate the different tectonic regimes present from early rifting to the formation of oceanic seafloor. This result together with magnetic data has been used to delimit the oceanic domain and compare with previous authors’ proposals. This method could be applied in any other basin or margin to help delimiting its boundaries. Finally, we analyze the role that an asthenospheric branch intruding from the Scotia Sea played in the evolution of the magnetic anomaly signature on an oceanic basin.